2008
DOI: 10.2147/tcrm.s2390
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative ileus: strategies for reduction

Abstract: Postoperative Ileus (POI) is a frequent, frustrating occurrence for patients and surgeons after abdominal surgery. Despite signifi cant research investigating how to reduce this multi-factorial phenomenon, a single strategy has not been shown to reduce POI's signifi cant effects on length of stay (LOS) and hospital costs. Perhaps the most signifi cant cause of POI is the use of narcotics for analgesia. Strategies that target infl ammation and pain reduction such as NSAID use, epidural analgesia, and laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Nanomollar EA fully recovered CCh-induced mI CAT suppressed by ketamine ( Figure 5C). These findings not only contribute to our better understanding of the limited usefulness of anticholinesterases (drugs that reduce breakdown of the physiological neurotransmitter acetylcholine) for the treatment of POI (Lubawski and Saclarides, 2008), but also show that the activity of the muscarinic cation channels initiating cholinergic excitation-contraction coupling in the gut could be restored by channel agonists that do not require activation of mAChRs and G-proteins.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Nanomollar EA fully recovered CCh-induced mI CAT suppressed by ketamine ( Figure 5C). These findings not only contribute to our better understanding of the limited usefulness of anticholinesterases (drugs that reduce breakdown of the physiological neurotransmitter acetylcholine) for the treatment of POI (Lubawski and Saclarides, 2008), but also show that the activity of the muscarinic cation channels initiating cholinergic excitation-contraction coupling in the gut could be restored by channel agonists that do not require activation of mAChRs and G-proteins.…”
Section: Discussionmentioning
confidence: 75%
“…Our interest has been prompted by the still unresolved problem of one of the GI motility disorders-postoperative ileus (POI), which imposes a significant economic burden on the healthcare system (Iyer et al, 2009) and for which there is no effective pharmacological treatment (Lubawski and Saclarides, 2008;Harnsberger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ramsey et al [ 64 ] found insulin-dependent diabetes to be a significant risk factor for the occurrence of ileus following colectomy (OR 1.40, 95% CI 1.30–1.49, p < 0.001). The increased occurrence of ileus after colectomy was attributed to damage to myenteric neurons from chronic diabetes [ 88 ], which is a common cause of diabetes-associated gastrointestinal complications. This is corroborated by previous studies which have suggested diabetes as a significant risk factor for postoperative ileus in abdominal surgery [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…After a major operation, conventional post-operative care usually includes restrict oral intake to prevent postoperative ileus and, thus, to protect surgical anastomoses [34]. The other reason for nil-by-mouth post operation is to allow anastomoses time to heal before being stressed by the food transiting the gut [35].…”
Section: Discussionmentioning
confidence: 99%